2018
DOI: 10.1007/s00705-018-3725-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of barley stripe mosaic virus isolates differing in their biological properties and the development of reverse transcription loop-mediated isothermal amplification assays for their detection

Abstract: Barley stripe mosaic virus (BSMV) is an important seed-transmitted pathogen occurring worldwide. Recently, the occurrence of mild BSMV pathotypes has been observed in barley crops in Poland. In this study, the full-length genome sequences of mild and aggressive Polish and German BSMV isolates was established. Phylogenetic and recombination analysis was performed using Polish and other BSMV isolates described to date. The analysis revealed that Polish isolates differed only in 25 nucleotides, which suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Therefore, Francois et al 30 and Hao et al, 31 working on the identification of wheat dwarf virus by LAMP, albeit without using Loop primers, demonstrated that 1 h of incubation was required for the amplification of the target gene. Similarly, as in the aforementioned studies, Zarzyńska-Nowak et al 32 used the technique for the detection of barley stripe mosaic virus (BSMV) infecting barley.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Francois et al 30 and Hao et al, 31 working on the identification of wheat dwarf virus by LAMP, albeit without using Loop primers, demonstrated that 1 h of incubation was required for the amplification of the target gene. Similarly, as in the aforementioned studies, Zarzyńska-Nowak et al 32 used the technique for the detection of barley stripe mosaic virus (BSMV) infecting barley.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex RT-PCR has been successfully applied for the screening and quantification of WSMV and TriMV [ 56 , 57 ], and RT-qPCR has been shown to be twice and thrice more sensitive than ELISA in the detection of TriMV and HPWMoV, respectively [ 58 ]. For BSMV, Zarzyńska et al demonstrated the limitations of ELISA as a diagnostic tool: it could not detect mild infections with moderate virus titers, while RT-PCR [ 59 ] and LAMP [ 60 ] were more sensitive. RT-qPCR is a valuable tool in studying virus gene expression and virus–host interactions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…LAMP amplifies target DNA at isothermal conditions (usually 60–65 °C) and obviates the need for thermal cyclers and postamplification procedures for signal detection. The significant advantages of LAMP assay make it very popular and widely used by many researchers to detect plant and animal viruses [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%